2017
DOI: 10.4103/ijmm.ijmm_17_102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Medically Important Candida Species by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism Analysis of the rDNA ITS1 and ITS2 Regions

Abstract: When the ability to identify Candida to species level of phenotypic and PCR-RFLP methods was assessed, a great difference was found between these two methods. It may be argued that Msp I and Bln I restriction enzyme fragments can be used in the identification of medically important Candida species. Further studies are needed to develop this kind of restriction profile to be used in the identification of candidal strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Aslani et al have also reported that C. albicans isolates are highly resistant to ITC, VRC, and FLU [ 64 ]. According to the findings of previous studies, resistance to azoles in C. glabrata has a multifactorial nature [ 65 ]. Based on the results of a study conducted by Amirrajab N. et al [ 66 ], the overall rates of resistance to ITC, VRC, and FLU were 72.5%, 47.5%, and 10% respectively, which are inconsistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Aslani et al have also reported that C. albicans isolates are highly resistant to ITC, VRC, and FLU [ 64 ]. According to the findings of previous studies, resistance to azoles in C. glabrata has a multifactorial nature [ 65 ]. Based on the results of a study conducted by Amirrajab N. et al [ 66 ], the overall rates of resistance to ITC, VRC, and FLU were 72.5%, 47.5%, and 10% respectively, which are inconsistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The most important mechanism of resistance to penicillin is beta-lactamase production, which inactivates penicillin by hydrolysis of its beta-lactam ring. Another mechanism is associated with penicillin-binding protein 2a (PBP2a), encoded by mecA [9]. MRSA strains carry the mecA gene, which is part of a larger piece of foreign DNA, known as the SCC mec element, which is not normally found in S. aureus.…”
mentioning
confidence: 99%
“…It may be argued that Msp I and Bln I restriction enzyme fragments can be used in the identification of medically important Candida spp. Further studies are needed to develop this kind of restriction profile to be used in the identification of candidal strains [237]. Restriction enzyme analysis of C. albicans and non- Candida albicans Candida spp.…”
Section: Molecular Methods Used To Detect Yeastsmentioning
confidence: 99%